Enhancing High School Student Engagement and Academic Achievement: The Analysis of the Practice Rehearsal Pairs Method - Sanjaya, Ibnuh; Ananda, Azwar; Al Rafni; Montessori, Maria; Hasrul (Edukasi, 2025)
Low student engagement and suboptimal academic achievement remain persistent challenges in secondary education. In response, this study aimed to examine the effectiveness of the Practice Rehearsal Pairs (PRP) method in simultaneously enhancing student engagement and academic performance in a physics learning context. Utilizing a quasi-experimental design with a non-equivalent control group, the study involved 72 tenth-grade students from State Senior High School 5 Tanjung Balai, divided equally into experimental and control classes. Data on student engagement were collected through structured observation using a five-category engagement rubric, while academic achievement was assessed through pretest and posttest scores. The analysis employed descriptive statistics, paired sample t-tests, normalized gain (N-Gain), and Multivariate Analysis of Variance (MANOVA) to determine both separate and simultaneous effects of the intervention. Findings revealed that the PRP method significantly improved student engagement, with the experimental group shifting from predominantly "very less active" to 94.45% categorized as "active" or "very active." Academic performance also increased markedly, with a mean posttest gain of 17.92 points and an N-Gain score of 0.5463, categorized as medium and quite effective. MANOVA results indicated a statistically significant simultaneous effect on both engagement and achievement (Wilks’ Lambda = 0.057, p < 0.001). These results suggest that PRP is an effective pedagogical strategy for fostering meaningful participation and cognitive gains in science education.